2020
DOI: 10.1007/s42770-020-00302-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic supplementation on oxidative stress markers in rats with diclofenac-induced hepatotoxicity

Abstract: In this study, we have investigated the effect of an antioxidant probiotic pretreatment toward an overdose of diclofenac in rats (100 mg/kg bw). Rats were treated daily with the probiotic Streptococcus salivarius St.sa (10 9 CFU) during seven successive days and then received a single treatment with diclofenac overdose in distilled water. Liver transaminases (alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase), histology, glutathione (GSH) and malondialdehyde (MDA) level were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The level of malondialdehyde (MDA) as an indicator of lipid peroxidation was evaluated using the thiobarbituric acid-reacting substances method (Riane et al, 2020). Briefly, the homogenized tissue sample was incubated with a thiobarbituric acid reagent for 30 min at 95 C. After cooling, it was centrifuged at 1500 × g for 10 min.…”
Section: Evaluation Of the Liver Oxidative Stressmentioning
confidence: 99%
“…The level of malondialdehyde (MDA) as an indicator of lipid peroxidation was evaluated using the thiobarbituric acid-reacting substances method (Riane et al, 2020). Briefly, the homogenized tissue sample was incubated with a thiobarbituric acid reagent for 30 min at 95 C. After cooling, it was centrifuged at 1500 × g for 10 min.…”
Section: Evaluation Of the Liver Oxidative Stressmentioning
confidence: 99%
“…[ 37 ] ALP levels increase during cellular damage, and this toxic effect can be induced by mitochondrial permeability transition and oxidative stress. [ 38 ] In this study, a significant increase in ALP level was observed in the BPA‐treated larvae group. Previous research has found that the BPA‐treated zebrafish embryo showed an increase in oxidative stress and ALP during the early embryonic stage.…”
Section: Discussionmentioning
confidence: 55%
“…And almost same results were observed in study by Tang et al, in neonatal rats. 13,14 Riane K et al 15 through his investigation has showed the effect of probiotics supplementation on oxidative stress markers in rats with diclofenac hepatotoxicity. Mice after treating with probiotic (Streptococcus salivarius) of concentration 10 9 CFU for seven successive days and then single treatment of diclofenac overdose with distilled water was given.…”
Section: Reducing the Oxidative Stressmentioning
confidence: 99%
“…On investigating the liver transaminases, histology, MDA (malondialdehyde) and GSH (glutathione), it shows that the pretreatment of mice with probiotics has reduced the diclofenac induced hepatotoxicity by enhancing hepatic markers, regulation of antioxidant expressions and their activities. 15 A study by Shang et al, has investigated the effect of probiotics on mercury (Hg), which is a poisoning agent in both animal and fishes. Mercury is a potential oxidative stress inducer, as it exerts high toxicity against enzymes involved in antioxidants regulation.…”
Section: Reducing the Oxidative Stressmentioning
confidence: 99%